Consensus for NF clinical trials: Recommendations of the REiNS collaboration (Supplement II). (16th August 2016) - Widemann, Brigitte C.; Plotkin, Scott R.
Abstract : The neurofibromatoses (NFs) can result in substantial morbidity in affected patients. In order to accelerate the development of effective therapies for NF-related tumor and nontumor manifestations, the development of standardized meaningful outcome measures for clinical trials is critical. The Response Evaluation in Neurofibromatosis and Schwannomatosis (REiNS) International Collaboration was established with the goal to develop consensus recommendations for outcome measures and endpoints in future NF trials and provided the first set of recommendations in a Neurology ® supplement in 2013. This second supplement updates on clinical trials that have incorporated the recommended measures and provides new recommendations for (1) standardized and specific cognitive assessment tools for use in NF clinical trials, (2) patient-reported outcome measures including pain and physical functioning, (3) functional outcome measures for airway plexiform neurofibromas, (4) the use of whole-body MRI in NF, and (5) the development of biomarkers in NF and guidelines for collection of biospecimens and establishment of biobanks for neurofibromatosis 1 (NF1), neurofibromatosis 2 (NF2), and schwannomatosis. Through engagement of the NF research community, regulatory agencies, NF advocacy groups, industry, and patients with NF, REiNS will provide a framework for comprehensive review of these recommendations, continue development of outcome measures relevant to patients, and compare results of trials, which use identical outcome measures.